2023
DOI: 10.1111/jhn.13206
|View full text |Cite
|
Sign up to set email alerts
|

A dietitian‐led coeliac service helps to identify and reduce involuntary gluten ingestion with subsequent reduction in the frequency of repeat endoscopies

Cristian Costas‐Batlle,
Nick Trott,
Yvonne Jeanes
et al.

Abstract: BackgroundDietitian‐led coeliac clinics have the potential to be a cost‐effective way of monitoring patients living with coeliac disease (CD). The aim of this service evaluation was to explore the impact of a dietitian‐led coeliac clinic on gluten‐free diet (GFD) adherence and the frequency of endoscopies with repeat duodenal biopsies.MethodsAdults with biopsy‐proven CD were transferred to a new dietitian‐led coeliac clinic where data were collected from medical records and analysed using SPSS. GFD adherence w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…In the UK, the dietitian’s role in supporting patients living with CeD has been explored using dietitian-led celiac clinics, where specialist dietitians become the leading healthcare provider supporting patients living with CeD, with support from a gastroenterologist when needed. A recent UK service evaluation [ 198 ] of a newly implemented dietitian-led celiac service found that it was associated with a significant reduction in both voluntary and involuntary gluten ingestion after all 170 patients had received dietary education from a specialist CeD dietitian. GFD adherence improvements happened despite patients being previously followed-up by a gastroenterologist or celiac nurse in the same hospital.…”
Section: Cost-efficacy Of Optimal Gfd Adherence Monitoringmentioning
confidence: 99%
“…In the UK, the dietitian’s role in supporting patients living with CeD has been explored using dietitian-led celiac clinics, where specialist dietitians become the leading healthcare provider supporting patients living with CeD, with support from a gastroenterologist when needed. A recent UK service evaluation [ 198 ] of a newly implemented dietitian-led celiac service found that it was associated with a significant reduction in both voluntary and involuntary gluten ingestion after all 170 patients had received dietary education from a specialist CeD dietitian. GFD adherence improvements happened despite patients being previously followed-up by a gastroenterologist or celiac nurse in the same hospital.…”
Section: Cost-efficacy Of Optimal Gfd Adherence Monitoringmentioning
confidence: 99%